Preservation of raw milk with lactoperoxidase/hydrogen peroxide/thiocyanate system, hydrogen peroxide system and by refrigeration - Barraquio, Virginia L.; Resubal, Lourdes E.; Bantoc, Isagani Benjamin M.; Almazan, Emerita N. (Asia life sciences :the international journal of life sciences.)
"The effectiveness of LP/H2O/SCN (LP) system for the preservation of raw milk was compared with refrigeration and H2O2 treatment. Standard plate count, acidity, resazurin, and clot-on-boiling tests indicated that using the LP system, raw milk processing may be delayed by up to 8 hours. Refrigeration was still the best method of preservation, with 100% of samples still acceptable after a 30-hour storage period. Cost calculation indicated that the LP system is cheaper and simpler to use than refrigeration."